Quality assessment of clinical guidelines for the treatment of obesity in adults: application of the AGREE II instrument - Erika Cardoso dos Reis; Sonia Regina Lambert Passos; Maria Angelica Borges dos Santos (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
There are various guidelines for the treatment of obesity, and thus the quality of these clinical guidelines has become a matter of concern. The objective was to describe and assess the quality of clinical guidelines for treatment of obesity in adults. We collected several studies, dated from 1998 to 2016, produced by different countries. The literature search included the National Guideline Clearinghouse (NGC), Guidelines International Network (GIN), PubMed (MEDLINE), Scopus, Web of Science, webpages of health institutions from different countries, and search sites, with the criterion: "clinical guidelines for treatment of obesity in adults and published until the 2016". The guidelines were assessed with the Appraisal of Guidelines for Research & Evaluation (AGREE II), according to the domains of the instrument. The search identified 21 guidelines: nine from Europe, six from North America, three from Latin America, and one each from Asia and Oceania and a transnational association. The Australian guideline had the best assessment. Of the six guidelines with the highest scores, five had been elaborated by the government sector responsible for the country's health. The domains "scope and purpose" and "clarity of presentation" had the highest score. Except for the Canadian guideline, the three guidelines drafted before the elaboration of AGREE II had the worst quality. In the domain "stakeholder involvement", only four guidelines (Australia, Scotland, France, and England) mentioned patient participation. Guideline development and quality enhancement are ongoing processes requiring systematic appraisal of the guideline production process and existing guidelines.